Myopia Control Combination to Slow The Progression of Myopia - Ashari, Ayu Devita (Syntax Literate, 2024)
Myopia is the most common refractive eye disorder in the world. Myopia is characterized by the inability of the eye to focus light on the retina, resulting in blurred distance vision. The purpose of this study is to understand the effectiveness of various methods or combinations of myopia control that can be used to slow or prevent the progression of myopia. This study used the Systematic Literature Review research method. The data collection technique in this study was carried out by literature study by exploring scientific journals, articles, books, and related publications contained in recognized databases, such as PubMed, Google Scholar, Scopus, and so on. The data that has been collected is analyzed through three stages, namely data reduction, data presentation and conclusion drawing. The results showed that the combination of controls to slow myopia include orthokeratology, environmental modification, low-level red-light therapy, antimuscarinic agents, increasing outdoor time and combination therapy.